Peran Kecerdasan Emosional, Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Unggul - Dewi, Rachmaniar Sari (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2024)
In a competitive work environment, superior performance is the key to individual and organizational success. This research explores the key role of emotional intelligence, work motivation, and job satisfaction in achieving superior performance in the workplace. The aim of this research is to identify the relationship between emotional intelligence, work motivation and job satisfaction with superior employee performance. This research also aims to provide insight into factors that can improve superior performance in the work environment. This research uses a quantitative approach by collecting data through questionnaires distributed to respondents consisting of employees at various levels in a company. Measurements were carried out using a Likert scale to measure the level of emotional intelligence, work motivation, job satisfaction and superior performance. The results of data analysis show that there is a positive relationship between emotional intelligence, work motivation and job satisfaction with superior employee performance. These findings indicate that psychological factors such as emotional intelligence and work motivation can contribute significantly to superior performance in the workplace.